A Narrow‐Bandgap n‐Type Polymer Semiconductor Enabling Efficient All‐Polymer Solar Cells. Issue 46 (30th September 2019) - Shi, Shengbin; Chen, Peng; Chen, Yao; Feng, Kui; Liu, Bin; Chen, Jianhua; Liao, Qiaogan; Tu, Bao; Luo, Jiasi; Su, Mengyao; Guo, Han; Kim, Myung‐Gil; et al.
Abstract: Currently, n‐type acceptors in high‐performance all‐polymer solar cells (all‐PSCs) are dominated by imide‐functionalized polymers, which typically show medium bandgap. Herein, a novel narrow‐bandgap polymer, poly(5, 6‐dicyano‐2, 1, 3‐benzothiadiazole‐ alt ‐indacenodithiophene) (DCNBT‐IDT), based on dicyanobenzothiadiazole without an imide group is reported. The strong electron‐withdrawing cyano functionality enables DCNBT‐IDT with n‐type character and, more importantly, alleviates the steric hindrance associated with typical imide groups. Compared to the benchmark poly(naphthalene diimide‐ alt ‐bithiophene) (N2200), DCNBT‐IDT shows a narrower bandgap (1.43 eV) with a much higher absorption coefficient (6.15 × 10 4 cm −1 ). Such properties are elusive for polymer acceptors to date, eradicating the drawbacks inherited in N2200 and other high‐performance polymer acceptors. When blended with a wide‐bandgap polymer donor, the DCNBT‐IDT‐based all‐PSCs achieve a remarkable power conversion efficiency of 8.32% with a small energy loss of 0.53 eV and a photoresponse of up to 870 nm. Such efficiency greatly outperforms those of N2200 (6.13%) and the naphthalene diimide (NDI)‐based analog NDI‐IDT (2.19%). This work breaks the long‐standing bottlenecks limiting materials innovation of n‐type polymers, which paves a new avenue for developing polymer acceptors with improved optoelectronic properties and heralds a brighter future of all‐PSCs. Abstract : Incorporating dicyanobenzothiadiazole into polymer yields an n‐type semiconductor DCNBT‐IDT, which exhibits a narrow bandgap of 1.43 eV and a high absorption coefficient of 6.15 × 10 4 cm −1 . The DCNBT‐IDT‐based all‐polymer solar cells achieve a remarkable power conversion efficiency of 8.32% with a small energy loss of 0.53 eV and a photoresponse of up to 870 nm.